The AcrySof Toric intraocular lens in subjects with cataracts and corneal astigmatism: a randomized, subject-masked, parallel-group, 1-year study - Holland, Edward; Lane, Stephen; Horn, Jeffrey D; Ernest, Paul; Arleo, Robert; Miller, Kevin M (Ophthalmology (Rochester, Minn.), 2010)
To compare the AcrySof Toric intraocular lens (IOL) and an AcrySof spherical control IOL and to investigate rotational stability of the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX) in subjects with cataracts and preexisting corneal astigmatism. Randomized, subject-masked, parallel-group, multicenter, 1-year study. We included 517 subjects (Toric IOL, n = 256; control IOL, n = 261). Unilateral implantation of an AcrySof Toric or AcrySof spherical control IOL (spherical powers, 12.00-25.00 diopters [D]; cylinder powers 1.50, 2.25, or 3.00 D for corneal astigmatism correction of 0.75 to < 1.50, ≥ 1.50 to <2.00, and ≥ 2.00 D with no upper limit, respectively). No limbal relaxing incisions were permitted. Visual acuity outcomes, IOL position, patient-reported spectacle use, and safety. One year postoperatively, best spectacle-corrected distance visual acuity of ≥ 20/20 was 77.7% (Toric IOL) versus 69.2% (control IOL). Uncorrected distance visual acuity of 20/20 or better was 40.7% (Toric IOL) versus 19.4% (control IOL; P<0.05). Mean absolute residual refractive cylinder was 0.59 D (Toric IOL) versus 1.22 D (control IOL; P<0.0001). Mean rotation was < 4° (range, 0°-20°) for the Toric IOL. Six-month spectacle freedom was 61.0% (Toric IOL) and 36.4% (control IOL; P < 0.0001). Complications in both groups were few and were as would be expected with cataract surgery. Favorable efficacy, rotational stability, distance vision spectacle freedom, and safety results support the use of the AcrySof Toric IOL for patients with cataracts and corneal astigmatism. Proprietary or commercial disclosure may be found after the references.